Dynamic Reversible Evolution of Solid Electrolyte Interface in Nonflammable Triethyl Phosphate Electrolyte Enabling Safe and Stable Potassium‐Ion Batteries. (24th April 2022) - Ji, Shunping; Li, Jielei; Li, Junfeng; Song, Chunyan; Wang, Shuo; Wang, Kexuan; Hui, Kwan San; Zha, Chenyang; Zheng, Yunshan; Dinh, Duc Anh; Chen, Shi; Zhang, Jintao; et al.
Abstract: Potassium‐ion batteries (PIBs) are a favorable alternative to lithium‐ion batteries (LIBs) for the large‐scale electrochemical storage devices because of the high natural abundance of potassium resources. However, conventional PIB electrodes usually exhibit low actual capacities and poor cyclic stability due to the large radius of potassium ions (1.39 Å). In addition, the high reactivity of potassium metal raises serious safety concerns. These characteristics seriously inhibit the practical use of PIB electrodes. Here, zinc phosphide composites are rationally designed as PIB anodes for operation in a nonflammable triethyl phosphate (TEP) electrolyte to solve the above‐mentioned issues. The optimized zinc phosphide composite with 20 wt% zinc phosphate presents a high specific capacity (571.1 mA h g −1 at 0.1 A g −1 ) and excellent cycling performance (484.9 mA h g −1 with the capacity retention of 94.5% after 1000 cycles at 0.5 A g −1 ) in the KFSI‐TEP electrolyte. XPS depth profile analysis shows that the improved cycling stability of the composite is closely related to the reversible dynamic evolutions and conversions of the sulfur‐containing species in the solid electrolyte interphase (SEI) during the charge/discharge process. This dynamic reversible SEI concept may provide a new strategy for the design of superior electrodes for PIBs. Abstract : Optimized zinc phosphide composites by controlling the raw materials are used as PIB anodes, showing high specific capacity (571.1 mA h g −1 ) and cycling stability (94.5% capacity retention after 1000 cycles) in the noninflammable triethyl phosphate electrolyte, and the improved cycling stability is due to the reversible dynamic evolutions and conversions of the sulfur‐containing species in the solid electrolyte interphase.